EFFECT OF NATIONAL DIGITALIZATION PROGRAMS ON SHADOW ECONOMY OF DEVELOPED COUNTRIES - Karimov Diyor Mukhtarovich; Amanova Maftuna Davlatboy kizi (Journals Park Publishing, 2024)
The article analyzes the relationship between digitalization and the shadow economy using the example of the experience of developed countries and their implementation of national programs for digitalization of the country's economy. The subject of consideration is a number of advantages of introducing digital technologies by public administration not only in the field of public administration, but also in the fields of education, entrepreneurship and society. Potential ways to reduce the scale of this phenomenon through digitalization are shown based on the experience of countries around the world.
Keywords: digital economy, digitalization, investments in IT, e-government, automated production, digital market, shadow economy, shadow labor market, digital shadow economy.